Regulation of decidualization and angiogenesis in the human endometrium: Mini review. Issue 5 (May 2014) - Okada, Hidetaka; Tsuzuki, Tomoko; Shindoh, Hisayuu; Nishigaki, Akemi; Yasuda, Katsuhiko; Kanzaki, Hideharu
Abstract Aim The human endometrium is a dynamic tissue that undergoes regular cycles of menstruation, menstrual repair, proliferation and secretory differentiation in response to hypoxia and the female sex hormones. Methods We identified new target genes that are regulated by progesterone during the decidualization of human endometrial stromal cells (ESC), including interleukin‐15 (IL‐15), fibulin‐1 (FBLN‐1), and heart and neural crest derivatives expressed transcript 2 (HAND2). Results IL‐15 is deeply involved in the hormonal control of the human endometrium by progesterone and may be important in embryo implantation. FBLN‐1 has been shown to be an important extracellular matrix that mediates progesterone action in human ESC differentiation toward implantation. Moreover, progestin‐induced HAND2 is a transcription factor that contributes to the increased levels of FBLN‐1 in human ESC. Several mediators, including vascular endothelial growth factor (VEGF), angiopoietin (ANGPT) and stromal cell‐derived factor 1 (SDF‐1), regulate human endometrial angiogenesis. Hypoxia increased the expression of VEGF and decreased the expression of SDF‐1 in ESCs. Furthermore, hypoxia reduced ANGPT1 levels in ESC; however, ANGPT2 levels were unaffected. Estradiol simultaneously induced the expressions of VEGF and SDF‐1, suppressing ANGPT1 production. Therefore, hypoxia and estradiol caused an increase in the ANGPT2/ANGPT1 ratio. Conclusion Hypoxia and female sex hormones are involved in the regulation of angiogenic factors in an independent manner in human ESC. Analysis of the process of decidualization and angiogenesis in the human endometrium would provide useful information for the fields of reproductive biology, regenerative medicine and tissue engineering.